2013
DOI: 10.1557/jmr.2013.282
|View full text |Cite
|
Sign up to set email alerts
|

Bulk response and grain boundary microelectrical activity of high TC BaTiO3–(Bi1/2K1/2)TiO3-based positive temperature coefficient of resistance ceramics

Abstract: Lead-free positive temperature coefficient of resistance (PTC) thermistors were synthesized from (1 À x/100)BaTiO 3 -(x/100)(Bi 1/2 K 1/2 )TiO 3 -based solid solutions, using a conventional mixed-oxide fabrication route, and sintered in N 2 followed by air annealing. A maximum T C of 205°C was achieved for x 5 20. An increase in x from 0 to 20 decreased the grain size by more than 92% and increased room temperature resistivity (q RT ) by 7 orders of magnitude. For x # 10, PTC ratio (q max /q min ) % 10 4.5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…263 Zubair et al also demonstrated the presence of a third electroactive component for BaTiO 3 À (Bi 0.5 K 0.5 )TiO 3 systems, which were doped with manganese and a Al 2 O 3 :SiO 2 :TiO 2 sintering aid and sintered in N 2 and reoxidized in air. 278,279 This third relaxation process was speculated to be due to the presence of a thin shell composed of barium vacancies (V 00 Ba ), which is formed between the grain and grain boundary region, and was only present above the Curie point at 170 C. The bulk grain semiconductivity was explained due to the reduction of Ti 4þ to Ti 3þ by V •• O , generated by sintering under an N 2 atmosphere. The grain boundary resistivity was attributed to a 2D layer of chemisorbed oxygen atoms and segregated Mn acceptor ions at the grain boundary.…”
Section: Impedance Spectroscopy Studiesmentioning
confidence: 99%
“…263 Zubair et al also demonstrated the presence of a third electroactive component for BaTiO 3 À (Bi 0.5 K 0.5 )TiO 3 systems, which were doped with manganese and a Al 2 O 3 :SiO 2 :TiO 2 sintering aid and sintered in N 2 and reoxidized in air. 278,279 This third relaxation process was speculated to be due to the presence of a thin shell composed of barium vacancies (V 00 Ba ), which is formed between the grain and grain boundary region, and was only present above the Curie point at 170 C. The bulk grain semiconductivity was explained due to the reduction of Ti 4þ to Ti 3þ by V •• O , generated by sintering under an N 2 atmosphere. The grain boundary resistivity was attributed to a 2D layer of chemisorbed oxygen atoms and segregated Mn acceptor ions at the grain boundary.…”
Section: Impedance Spectroscopy Studiesmentioning
confidence: 99%
“…However, the room temperature resistance (R 25 ) and T c of BT elements generally rise together with increasing KBT concentration [12,13] for KBT's decomposition and volatilization in synthesis process [14,15]. In fact, magnitude of R 25 usually limits the application range of lead free devices and ultra high R 25 or electrical insulation will restrict further KBT addition.…”
Section: Introductionmentioning
confidence: 99%